Pengaruh Perputaran Kas, Struktur Modal, Perputaran Persediaan, Asset Growth Dan Total Asset Turnover terhadap Profitabilitas - Jihan Nafi'ah; Gendro Wiyono; Ratih Kusumawardhani (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
This study aims to analyze the effect of Cash Turnover, Capital Structure (DER), Inventory Turnover, Asset Growth and Total Asset Turnover (TATO) on Profitability (ROA). The type of research used is quantitative research. The sampling method in this study used a purposive sampling technique. The sample used is 5 automotive and component companies listed on the Indonesia Stock Exchange for the period 2012-2019. Data were analyzed by multiple linear regression analysis method and classical assumption test obtained using SPSS version 25 program. The results showed that cash turnover partially had a negative and significant effect on profitability (ROA), capital structure (DER) partially had a positive and significant effect. on profitability (ROA), inventory turnover partially negative and significant effect on profitability (ROA), asset growth partially positive and significant effect on profitability (ROA) and total asset turnover (TATO) partially positive and significant effect on profitability (ROA ). The results of the study simultaneously show that the variables of cash turnover, capital structure (DER), inventory turnover, asset growth and total asset turnover (TATO) have a positive and significant effect on profitability (ROA). Keywords: Cash Turnover, DER, Inventory Turnover, Asset Growth, TATO, ROA